Fuel lifetime extension for the KLT-40S small modular reactor by means of thorium-uranium fuel cycle; Annals of Nuclear Energy; Vol. 192 - Belyavsky S. V. Sergey Vladimirovich; Balachkov M. M. Maxim Mikhailovich; Danilenko V. O. Vitaly Olegovich; Nesterov V. N. Vladimir Nikolaevich (2023, 2023)
Title screen